Factors affecting the quality of university accounting education in the context of industry 4.0: An empirical study at universities in Vietnam - Thuy, Lai Thi Thu (Edelweiss Applied Science and Technology, 2024)
This study examines the factors influencing the quality of accounting education at universities in Vietnam in the context of Industry 4.0. The research model includes four main factors: curriculum, lecturer expertise, facilities and technology, and industry linkages. A survey of 217 students found that lecturer expertise had the most significant impact on the quality of education, followed by curriculum, industry linkages, and facilities. These factors are essential for enhancing students' practical skills, the application of technology, and meeting labor market demands. The study also suggests that universities should strengthen collaboration with businesses to provide students with real-world exposure, update curricula to better integrate theory and practice, and invest in modern facilities and accounting software. These recommendations are aimed at improving the overall quality of accounting education, ensuring that students develop both professionally and technically, and are well-prepared for the challenges posed by the digital transformation in the accounting industry.